2018
DOI: 10.1080/17429145.2018.1441450
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing plant-bacteria-fungi interactions to improve plant growth and degradation of organic pollutants

Abstract: Exploiting the potential of bacteria in phytoremediation for the removal of organic and inorganic pollutants from soils and (ground)water holds great promise. Besides bacteria, mycorrhizal fungi and free-living saprotrophs are well known for their strong degradative capacities and plant growth promotion effects, which makes them of high interest for use in different bioremediation strategies. To further increase the efficiency and successes of phytoremediation, interactions between plants and their associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 132 publications
(172 reference statements)
0
19
0
Order By: Relevance
“…They interact with each other via diverse mechanisms ranging from trophic interactions to biofilm formation and even the interchange of genetic information, to name just a few [1,2]. These interactions are receiving increasing attention as we understand more about how the roles of fungi and bacteria as decomposers, nitrogen fixers, pathogens, and mutualistic partners of plants and animals are modified by fungus-bacterium interactions [3][4][5][6][7][8].…”
Section: Microbial Ecology Of Floral Nectarmentioning
confidence: 99%
“…They interact with each other via diverse mechanisms ranging from trophic interactions to biofilm formation and even the interchange of genetic information, to name just a few [1,2]. These interactions are receiving increasing attention as we understand more about how the roles of fungi and bacteria as decomposers, nitrogen fixers, pathogens, and mutualistic partners of plants and animals are modified by fungus-bacterium interactions [3][4][5][6][7][8].…”
Section: Microbial Ecology Of Floral Nectarmentioning
confidence: 99%
“…Plant-root associated microbes have been identified as major contributors to plant survival and health [1], as they can increase growth through a myriad of functions like the secretion of compounds such as phytohormones, organic acids, and antibiotics, thus improving access to nutrition and resistance to pathogens [2][3][4][5]. Moreover, in polluted environments, microorganisms can alleviate soil toxicity by reducing contaminant levels and/or bioavailability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It may be due to the combined effect of both plant and hydrocarbon bacteria. It has been reported that in the presence of the microorganism, plants get enough support in severe conditions and can perform better organic pollutant degradation [33,34]. It has also been noted that the root exudates secreted by the plant, boost up the growth and activity of rhizosphere bacterial communities [35].…”
Section: Hydrocarbons Degradationmentioning
confidence: 99%